Teaching Competency Needs of Vocational Agriculture Teachers as Perceived by Vocational Agriculture Teachers and Administrators in Thailand - Tipanark, Peerapong (1991)
The purpose o f this study was to determine the teaching competency needs of vocational agriculture teachers at the agricultural college level in order to provide information as input to programme planning of agricultural education in Thailand. Data were gathered from 304 vocational agriculture teachers and 180 administrators in the 43 agricultural colleges in Thailand. Two instruments were constructed to gather the data: (1) an eight item questionnaire regarding the teachers' and the administrators' personal characteristics backgrounds; (2) a 76 item inventory of vocational agriculture teachers' teaching competencies covering five competency areas. Data collected from the inventory were analysed to determine in - service programme need priorities. The respondents were requested to rate the competencies on a five - point Likert - type scale for the level of importance and attainment. In order to determine need priorities, a need indicator score was calculated for each item by dividing the square of the importance rating by the attainment rating. Finally, for the ratings of importance and attainment, the need indicator s core was arranged in rank order for both the respondent groups according to items and competency areas. Spearman's Coefficient of correlation was used to calculate the level of agreement be tween the groups' rank order. In addition, correlational analysis was carried out to determine the relationships between some selected personal characteristics of the teachers and their teaching competency needs.